Best easy day hikes. Yellowstone National Park 2024 - Schneider, Bill (Best easy day hikes series., 2024)
"Geysers, paint pots, and glowing blue pools; deep canyons with plunging waterfalls; broad river valleys with seemingly endless views; and tall rugged mountains -- Yellowstone National Park is a hiker?s paradise with more than 800 miles of trails. This updated edition of the classic guidebook has everything you need to explore the best easy day hikes in this gorgeous national treasure."--Provided by publisher.